2014
DOI: 10.1021/es501903b
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Hormonal Network and the Enantioselectivity of Bifenthrin in Trophoblast: Maternal–Fetal Health Risk of Chiral Pesticides

Abstract: Endocrine-disrupting chemicals (EDCs) can interfere with normal hormone signaling to increase health risks to the maternal-fetal system, yet few studies have been conducted on the currently used chiral EDCs. This work tested the hypothesis that pyrethroids could enantioselectively interfere with trophoblast cells. Cell viability, hormone secretion, and steroidogenesis gene expression of a widely used pyrethroid, bifenthrin (BF), were evaluated in vitro, and the interactions of BF enantiomers with estrogen rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…As the different interactions with biological macromolecules like enzymes and nucleic acids, enantiomers of chiral herbicides may show opposite herbicidal activity though sharing the same physical and chemical properties (Diao et al, 2010;He et al, 2015;Liu et al, 2013;Liu et al, 2012;Wen et al, 2011;Zhao et al, 2014). In the present study, the DCPP enantiomers showed obvious enantioselective toxicity, which was consistent with previous studies (Wen et al, 2010;Wu et al, 2011).…”
Section: Enantioselective Effect Of Dcpp On Plant Growthsupporting
confidence: 91%
“…As the different interactions with biological macromolecules like enzymes and nucleic acids, enantiomers of chiral herbicides may show opposite herbicidal activity though sharing the same physical and chemical properties (Diao et al, 2010;He et al, 2015;Liu et al, 2013;Liu et al, 2012;Wen et al, 2011;Zhao et al, 2014). In the present study, the DCPP enantiomers showed obvious enantioselective toxicity, which was consistent with previous studies (Wen et al, 2010;Wu et al, 2011).…”
Section: Enantioselective Effect Of Dcpp On Plant Growthsupporting
confidence: 91%
“…Reverse transcription of 0.5 mg of total RNA was performed for the synthesis of the first-strand complementary DNA using the ReverTra Ace 1 qPCR RT kit (Toyobo) [39]. The relative levels of mRNA were normalized to the housekeeping gene b-actin and calculated using the 2 -DDCT method [42]. The oligonucleotide primers for each gene were designed using OMIGA Ver 2.0 software (Oxford Molecular) and are presented in the Supplemental Data, Table S1.…”
Section: Gene Expression Assaymentioning
confidence: 99%
“…Enantiomers of chiral compounds often exhibit different biological effects, i.e., enantioselective biochemical and toxicological effects . Such stereospecific biological effects have drawn much attention from researchers from the environmental field as well as people from the pharmaceutical and pesticide industries .…”
mentioning
confidence: 99%
“…Enantiomers of chiral compounds often exhibit different biological effects, i.e., enantioselective biochemical and toxicological effects. [1][2][3][4][5][6][7] Such stereospecific biological effects have drawn much attention from researchers from the environmental field as well as people from the pharmaceutical and pesticide industries. 8,9 Therefore, many studies had investigated the effect of chiral compounds of environmental interest, not only on their ecological and health risk but also on their enantioselectivity including a wide range of persistent contaminants such as organochlorine pesticides (e.g., DDTs) and PCBs as well as emerging contaminants such as pharmaceuticals, phthalates, and particularly new pesticide substitutes.…”
mentioning
confidence: 99%